The effects of a series of carbon dots on fibrillation and cytotoxicity of human islet amyloid polypeptide. Issue 28 (4th July 2016) - Wang, Li; Zhu, Shoujun; Lu, Tong; Zhang, Guangji; Xu, Jia; Song, Yubin; Li, Yang; Wang, Liping; Yang, Bai; Li, Fei
Abstract : Carbon dots can change hIAPP aggregation kinetics and have a potential to reduce the cytotoxicity of the polypeptide. Abstract : Carbon dots (CDs) have been widely used as candidates for drug carriers and bio-imaging probes because of their high drug loading capacity and intrinsic fluorescence property, as well as their good biocompatibility. In this study, the potential role of CDs in regulating the aggregation behavior of human islet amyloid polypeptide (hIAPP) was explored for the first time. Five kinds of CDs belonging to three categories, namely polymer dots (PDs-1 and PDs-2), carbon nanodots (CNDs and CQDs), and graphene quantum dots (GQDs), were prepared and characterized. The fibrillation behaviors of hIAPP in the presence of these CDs were monitored by the ThT assay and TEM/AFM imaging, and the cytotoxicity of the systems was tested by the MTT and LDH release assays. Our results showed that the polymer dots and carbon nanodots inhibit hIAPP fibrillation, while the GQDs promoted the formation of hIAPP fibrils. The PDs and GQDs that were nontoxic in INS-1 cells exerted effects leading to decreasing cell death induced by hIAPP through different mechanisms. The inhibitory activity and mechanism of the CDs were closely associated with their structures and surface properties. Our results shed light on a new potential application of CDs in therapeutics.